1987
DOI: 10.1210/mend-1-8-542
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Cytochrome P450j Messenger Ribonucleic Acid in the Diabetic Rat

Abstract: Cytochrome P450j, an enzyme involved in nitrosamine metabolism, is expressed in hepatic, pulmonary, and renal tissues and its level is elevated in ethanol- and acetone-treated rats as well as in diabetic rats induced by either streptozotocin or alloxan. Although P450j protein is substantially elevated by all inducing regimens, only in diabetic rats is P450j mRNA increased 10-fold. Nuclear run-on transcription analysis showed that this mRNA increase is not due to transcriptional activation but is due to specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(72 citation statements)
references
References 33 publications
5
67
0
Order By: Relevance
“…Additional pro-oxidants in fatty livers might be produced via the cytochrome P 450 system. Increased hepatic cytochrome P450 II E has been reported in diabetes 31 and on diets that induce either choline deficiency 32 or obesity, 33 conditions associated with increased concentrations of fatty acids in the liver similar to obese Zucker rats.…”
Section: Discussionmentioning
confidence: 99%
“…Additional pro-oxidants in fatty livers might be produced via the cytochrome P 450 system. Increased hepatic cytochrome P450 II E has been reported in diabetes 31 and on diets that induce either choline deficiency 32 or obesity, 33 conditions associated with increased concentrations of fatty acids in the liver similar to obese Zucker rats.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported that the induction of CYP2E1 seems to be regulated at the post-transcriptional or post-translational levels by the stabilization of mRNA [4] or protection against the rapid degradation of protein [5,19]. To obtain a clue towards understanding the mechanisms, we investigated the possibility that miRNAs may be involved in the regulation of human CYP2E1.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the induction of CYP2E1 protein by these chemicals was not necessarily accompanied by an increase of CYP2E1 mRNA level [3]. The proposed mechanisms for the induction of CYP2E1 are the stabilization of mRNA [4] or protein [5]. Previously, Sumida et al [6] reported that the CYP2E1 mRNA levels in 15 human liver samples were not positively correlated with the chlorzoxazone 6-hydroxylase activities, which is a probe activity of CYP2E1.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of CYP2E1 is considered to involve multiple mechanisms including transcriptional activation (Ueno and Gonzalez, 1990), stabilization of mRNA (Song et al, 1987), posttranslational modifications (Song et al, 1989), and substrate stabilization of the protein against degradation (Eliasson et al, 1988). The induction of hepatic CYP2E1 proteins by ethanol can occur at transcriptional and/or post-transcriptional levels; ligandmediated protein stabilization is thought to be the primary mechanism at relatively low ethanol doses (Eliasson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%